2019
DOI: 10.3390/jcm8010033
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in ERCC5 rs17655 and ERCC1 rs735482 Genes Associated with the Survival of Male Patients with Postoperative Oral Squamous Cell Carcinoma Treated with Adjuvant Concurrent Chemoradiotherapy

Abstract: The nucleotide excision repair (NER) pathway plays a major role in the repair of DNA damaged by exogenous agents, such as chemotherapeutic and radiotherapeutic agents. Thus, we investigated the association between key potentially functional single nucleotide polymorphisms (SNPs) in the NER pathway and clinical outcomes in oral squamous cell carcinoma (OSCC) patients treated with concurrent chemoradiotherapy (CCRT). Thirteen SNPs in five key NER genes were genotyped in 319 male OSCC patients using iPLEX MassARR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…As there are many SNPs in the ERCC1 gene and only a few SNPs may contribute to the occurrence of cancer, it is extremely important to choose the right candidate polymorphisms to test an association with OSCC. In view of the previous reports, we chose four SNPs in the ERCC1 gene including rs11615, rs3212948, rs3212961, and rs735482 which are reported to be associated with certain cancers [ 12 , 13 , 20 , 23 ]. In our study, we did not found a significant association between four SNPs in the ERCC1 gene and susceptibility of OSCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As there are many SNPs in the ERCC1 gene and only a few SNPs may contribute to the occurrence of cancer, it is extremely important to choose the right candidate polymorphisms to test an association with OSCC. In view of the previous reports, we chose four SNPs in the ERCC1 gene including rs11615, rs3212948, rs3212961, and rs735482 which are reported to be associated with certain cancers [ 12 , 13 , 20 , 23 ]. In our study, we did not found a significant association between four SNPs in the ERCC1 gene and susceptibility of OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis, it was concluded that ERCC1 C118T (rs11615) and C8092A could predict both the objective response rate as well as overall survival for platinum-based chemotherapy in Asian NSCLC patients through the analysis of 33 studies including 5373 patients [ 22 ]. One study from Taiwan found that the ERCC1 rs735482 CC genotype is associated with an increased risk of recurrence in male patients with OSCC treated with concurrent chemoradiotherapy [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects with low expression and/or activity of DNA repair enzymes have impaired ability to remove tobacco-induced DNA damage and are more likely to develop lung cancer. Excision repair cross complementing group 1 (ERCC1) and X-ray repair crosscomplementing group 1 (XRCC1) enzymes are needed to clear DNA damage and have been highlighted as potential biomarkers of clinical outcome in cancer [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, Wang and colleagues provided evidence showing that XPC rs2228000 genotypes have conferred a protective effect on oral cancer susceptibility, evident in older individuals, women, ever smokers, and never drinkers (20). In 2019, Senghore and colleagues found that the TT genotype at XPC rs2228000 increased the risk of poor overall survival at borderline significance compared to the CC+CT genotypes (HR=1.86, 95% CI=0.97-3.56), while XPC rs2228000 or XPC rs2228001 genotypes could not serve as good predictors for oral cancer susceptibility (21). Based on the limited literature on XPC and oral cancer, we are keen to assess whether rs2228000 and rs2228001 polymorphisms of XPC are associated with the risk of oral cancer in Taiwan.…”
mentioning
confidence: 99%